Proceedings of the 2016 International Conference on Computer Science and Electronic Technology 2016
DOI: 10.2991/cset-16.2016.7
|View full text |Cite
|
Sign up to set email alerts
|

How to Test Location-based Mobile Apps

Abstract: Location-based services are growing in popularity due to the ubiquity of smartphone users. The availability and validity of location-based services are often effected by mobile user location contexts, which make mobile location-based services testing becomes one urgent and challenging issue. In this paper, we analyze location related features for location-based mobile apps. Then some test strategies are proposed to test those location related features and characteristics. Moreover, a case study is reported to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Based on the findings of the study, the following can be concluded: (1) The mobile application, "TIP Express", was able to simulate and visualize route/path for T.I.P. Quezon City Campus; (2) The mobile application gives the current location of the user and a list of college buildings where he/she may want to go by the use of fuzzy logic algorithm; and (3) TIP Express is acceptable in terms of functional suitability, reliability and efficiency which are software quality factors based on ISO-25010.…”
Section: Summary Conclusion and Recommendationmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on the findings of the study, the following can be concluded: (1) The mobile application, "TIP Express", was able to simulate and visualize route/path for T.I.P. Quezon City Campus; (2) The mobile application gives the current location of the user and a list of college buildings where he/she may want to go by the use of fuzzy logic algorithm; and (3) TIP Express is acceptable in terms of functional suitability, reliability and efficiency which are software quality factors based on ISO-25010.…”
Section: Summary Conclusion and Recommendationmentioning
confidence: 97%
“…All these things are done with the help of smartphones. Likewise, technology is very helpful for the people who want to be aware of their location [2]. Most often, mobile users do not know the exact place they are in.…”
Section: Introductionmentioning
confidence: 99%